Impact of Calorie Intake on Cardiovascular Disease Risk Factors for Young Adults Working from Home During the COVID-19 Pandemic - Mukhtar, Diniwati; Ridwan, Karina A. D. A.; Fitriani, Hasna L. (Universitas Sam Ratulangi, 2025)
Abstract: During the COVID-19 pandemic, working from home (WFH) led to increased passivity, potentially affecting body mass index (BMI), waist circumference (WC), and blood pressure (BP) values, which are risk factors for cardiovascular disease (CVD). This study aimed to determine the impact of calorie intake on these risk factors in young adults working from home during the COVID-19 pandemic. This experimental study employed a one-group pre- and post-test design conducted over two months. Respondents' daily physical activities were recorded using Bouchard's questionnaire, and a food record method was used to document all foods consumed over three days. The study followed up with respondents for two months. The results indicated that respondents with good physical activity levels experienced a decrease in BMI: 53.3% of men and 37.5% of women. Adequate calorie intake also contributed to a decrease in BMI, with 53.3% of men and 57.1% of women showing reductions. However, the t-test showed p-values >0.05 for the correlations between calorie intake and BMI, WC, systolic blood pressure (SBP), and diastolic blood pressure (DBP). In conclusion, there was no significant impact of calorie intake on risk factors for CVD, such as obesity and high blood pressure. Nonetheless, it was observed that appropriate calorie intake could potentially prevent the increase of these risk factors. Keywords: calorie intake; cardiovascular disease; COVID-19 pandemic